Tenting on the Plains — 1883 - Libbie Custer (Symphony in the Flint Hills, 2013)
Excerpt from "Tenting on the Plains — 1883." A story from Libbie Custer, Lieutenant Colonel George Custer's wife, telling the story of their time at Ft. Riley and the area around it.
Keywords: Libbie Custer; wife; George Custer; Ft. Riley; army; military; tenting; adventure; fresh; nature; prairie; grassland; wild; freedom; riding; horses; Plains; General Sherman; imagery; description; descriptive; story; real life; young